Azobenzene-decorated cellulose nanocrystals as photo-switchable chiral solutes in nematic liquid crystals. Issue 48 (25th November 2022) - Sezgin, Barış; Hegmann, Torsten
Abstract : Cellulose nanocrystals, surface-decorated with azobenzenes, are introduced as chiral solutes with molecular and morphological chirality and bestowed with the ability to photoswitch the helical pitch of induced chiral nematic liquid crystal phases. Abstract : In this work, we validate that cellulose nanocrystals (CNCs), surface-functionalized with pro-mesogenic azobenzene pendants, can act as photoswitchable chiral solutes in a nematic liquid crystal (N-LC). Upon UV illumination, the helical pitch and thus the helical twisting power ( β w ) can be altered based on the trans – cis photoisomerization of the azobenzene pendants. This approach shows that CNCs—biorenewable chiral additives with a commensurate, rod-like shape to N-LC molecules—can be adapted just like common small molecule organic chiral solutes in LC phases based on simple surface modifications.